Aplikasi Pupuk Organik Cair Berbahan Limbah Kulit Buah Aren (Arenga pinnata Merr.) Untuk Meningkatkan Potensi Pertumbuhan dan Hasil Kedelai Di Tanah Ultisol - Dian Novita; Bambang Wijaya Kusuma; Edi Susilo (University of Prof. Dr. Hazairin, SH, 2017)
One of the causes have not met national food needs, especially soybeans is still low and the productivity of agricultural land are limited. Factors causing lower soybean production Indonesia is a way of farming and land area is narrow. It required the intensification of productive agricultural land and expansion. One solution to increase land productivity by intensifying the system of fertilizing with organic fertilizers. Giving input in the form of organic fertilizer on soil ultisol can change and improve soil properties, physical, chemical and biological soil. One source of organic fertilizer from waste leather palm.The purpose of this study was to obtain preliminary information the best use of liquid organic fertilizer made from waste leather palm fruit in some soybean varieties in the ground ultisol Bengkulu. Outcomes resulting from this research is 1). Solving the problems experienced in soybean cultivation in soil that is expensive and limited ultisol inorganic fertilizers, 2). Getting the best organic fertilizer products made from waste leather palm fruit.The results showed that the treatment of varieties showed significant effect on the high variable plants aged 1 MST, 3 MST, number of leaves 2 MST, 3 MST, 4 MST and 5 MST, branch number 2 MST and 4 MST, pods total, the number of empty pods and number of pods pithy. Varieties Detam 2, Malika and Ceneng produce components of growth and better results. At the dosage of liquid organic fertilizer showed significant effect on the number of empty pods. Control treatment and dosage of 200 ml / plant produces the number of empty pods fewer. There is no significant interaction effects between varieties and dosage POC on growth variables and soybean yields.